Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.

Activity modulated low platium content oxygen reduction electrocatalysts prepared by inducing nano-order dislocations on carbon nanofiber through N-2-doping - Palaniselvam, Thangavelu; Irshad, Ahamed; Unni, Bipinlal; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
We demonstrate how surface unsaturation developed during small order buckling of graphene interlayer upon doping iron nitride (i.e., FeNx) moieties in carbon nanofiber can be utilized as a very efficient mode of surface activation to establish fine distribution of Pt nanoparticles with 10 wt %. The surface dislocations have been effectively modulating the oxygen reduction characteristics of Pt through synergistic effects of the interacting species. The simultaneous enhancement of dispersion of Pt and oxygen reduction reaction (ORR) activity with a low weight percentage of dispersed Pt has been attained by FeNx doping, which increases the density of the active sites owing to the formation of fine and abundant delaminated regions on the CNF surface. HR-TEM images clearly depict the fine distribution of Pt nanoparticles on the delaminated regions of FeNxCNF. The stable incorporation of Pt on nitrogen doped active sites has been further confirmed by observing the formation of Pt-N peak at 391.5 eV using XPS analysis. The fine distribution of Pt nanoparticles along the abundant nanopockets between the buckled graphene layers helped the system to attain significantly high electrochemically active surface area of Pt as evident from the cyclic voltammetric studies. The mass activity of PtFeNxCNF at 0.9 V vs RHE is 4.9 mA mgPt(-1) which is two times higher than that of E-TEK. The superior catalytic activity (exchange current density (i(0)) at 0.8 V is 2.61X 10(-6)) could be further confirmed by single cell evaluation of the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC), where the cathode electrode was fabricated from this new catalyst.

Activated nitrogen doped graphene shell towards electrochemical oxygen reduction reaction by its encapsulation on Au nanoparticle (Au@N-Gr) in water-in-oil ``nanoreactors'' - Dhavale, Vishal M.; Gaikwad, Sachin S.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2014)
Encapsulation of nitrogen doped graphene on Au nanoparticle (Au@N-Gr) could be accomplished through a water-in-oil emulsion technique, where the emulsion droplets act as `nanoreactors' and the redox reaction inside the droplets results in the formation of core-shell nanoparticles. The encapsulation of N-Gr on a small quantity of Au (N-Gr : Au wt ratio of 90 : 10) made the N-Gr layer more conductive and active towards electrochemical oxygen reduction reaction (ORR). The enhanced conductivity helped the system narrow down the ohmic overpotential, and direct electronic interactions between the Au and Gr layers brought in a favourable positive shift to the onset potential for ORR. Encapsulation has helped N-Gr reduce the overpotential by similar to 121 mV as compared to N-Gr alone. Apart from this, the oxygen reduction kinetics of Au@N-Gr also appeared to be superior to N-Gr and Au nanoparticles as separate entities due to greater involvement of the preferred 4-electron reduction pathway. At -0.3 V (vs. Hg/HgO), the percentage of hydrogen peroxide (H2O2) (a product formed from the undesirable 2-electron reduction pathway) was found to be 16.5% for Au@Gr, where Au was covered with undoped Gr, which gets reduced to a significantly low level of 6.5% for Au@N-Gr. Au and N-Gr as separate entities give yield of H2O2 as 52.2 and 47.7%, respectively. From these, it can be concluded that the coverage of N-Gr on Au helps decrease the yield of H2O2 drastically apart from the benefits of synergistic interactions in reducing both ohmic and activation overpotentials.

All-solid-state-supercapacitor and a process for the fabrication thereof - Kurungot, Sreekumar; Badiger, Manohar V.; Anothumakkool, Bihag; Torris, Arun (WO2014170912 A1, 2014)
The present invention discloses. all-solid-state supercapacitor (ASSP) with enhanced electrode-electrolyte interface which gives highest very high specific capacitance, areal capacitance and shows very low internal resistance (ESR). The invention particularly discloses the fabrication of all-solid-state supercapacitor by intercalation of solid state polymer electrolyte inside the conducting porous substrate coated with a charge storage electrode material to achieve the desired effect.

Activity tuning of cobalt ferrite nanoparticles anchored on N-doped reduced graphene oxide as a potential oxygen reduction electrocatalyst by Zn substitution in the spinel matrix - Kashyap, Varchaswal; Singh, Santosh K.; Kurungot, Sreekumar (Chemistry Select, 2017)
Development of highly efficient and durable ORR catalysts by using non-platinum group metals (such as Co, Fe, Mn, and Zn) is a challenging task in the forward path towards the realization of low-cost energy devices in the commercial stream. The present work deals with an effective strategy wherein an efficient Pt-free electrocatalyst for oxygen reduction reaction (ORR) is prepared by stoichiometrically substituting some fraction of Fe with Zn in cobalt ferrite and anchoring these spinel nanoparticles on nitrogen doped reduced graphene oxide (N-rGO). Zn substitution is found to be significantly altering the ratio of Fe2+/Fe3+ in the cobalt ferrite nanocrystal system with a concomitant promotional influence on its electrocatalytic activity towards ORR. The nanoparticle composition with a Co, Fe and Zn molar ratio of 1.0:1.7:0.3, represented by the formula CoFe1.7Zn0.3O4(CFZn(0.3)), supported over N-rGO has shown 10 mV and 20 mV positive shift in the onset and half-wave potentials, respectively, for ORR in 0.1 M KOH in comparison to the nanoparticles of CoFe2O4 supported over N-rGO (CF/N-rGO). The optimum Zn substitution is found to be narrowing down the difference with the state-of-the-art Pt/C for ORR by 100 and 110 mV in terms of the onset and half-wave potentials, respectively. Most significantly, the homemade catalyst is found to be clearly outperforming the Pt catalyst in terms of the limiting current density and electrochemical durability.
Keywords: Carbon Nano-fiber; Cathod Catalyst; CoFe2O4; Evolution; Magnetic-properties; Membrane fuel- Cell; Metal-Air Batteries; N-doped graphene; Nanocrystalline; nanocrystals; oxygen reduction reaction; performance; Platinium; solvothermal synthesis; Zn substituted cobalt ferrite

Air-cathode interface-engineered electrocatalyst for solid-state rechargeable zinc-air batteries - Manna, Narugopal; Singh, Santosh K.; Kurian, Maria; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2022)
Solid-state rechargeable zinc-air batteries (ZABs) are gaining interest as a class of portable clean energy technology due to their advantages such as high theoretical energy density, intrinsic safety, and low cost. It is expected that an appropriately triple-phase boundary (TPB) engineered, bifunctional oxygen reaction (OER and ORR) electrocatalyst at the air- electrode of ZABs can redefine the performance characteristics of these systems. To explore this possibility, an electrode material consisting of manganese- cobalt-based bimetallic spinel oxide (MnCo2O4)-supported nitrogen-doped entangled graphene (MnCo2O4/NEGF) with multiple active sites responsible for facilitating both OER and ORR has been prepared. The porous 3D graphitic support significantly affects the bifunctional oxygen reaction kinetics and helps the system display a remarkable catalytic performance. The air electrode consisting of the MnCo2O4/NEGF catalyst coated over the gas diffusion layer (GDL) ensures the effective TPB, and this feature works in favor of the rechargeable ZAB system under the charging and discharging modes. As an important structural and functional attribute of the electrocatalyst, the porosity and nitrogen doping in the 3D conducting support play a decisive aspect in controlling the surface wettability (hydrophilicity/hydrophobicity) of the air electrode. The fabricated solid-state rechargeable ZAB device with the developed electrode displayed a maximum peak power density of 202 mW cm(-2), which is significantly improved as compared to the one based on the Pt/C + RuO2 standard catalyst pair (124 mW cm(-2)). The solid-state device which displayed an initial charge-discharge voltage gap of only 0.7 V at 10 mA cm(-2) showed only a small increment of 86 mV after 50 h.
Keywords: air-cathode interface; bifunctional oxygen catalyst; N-doped entangled graphene; solid-state zinc-air battery; spinel oxides

Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Advanced 3D network of N-doped graphitic carbon with FeNi alloy embedding for high-performance rechargeable Zn-air batteries - Pandikassala, Ajmal; Kurian, Maria; Gangadharan, Pranav K.; Torris, Arun; Kurungot, Sreekumar (Advanced Sustainable Systems, 2024)
Despite the significant progress in Zn-air batteries (ZABs), their widespread use in the rechargeable sector is hindered due to the scarcity of efficient bifunctional oxygen catalysts that can catalyze both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). To address this, an ORR/OER bifunctional electrocatalyst is designed with ultrafine alloyed FeNi nanoparticles encapsulated in a 3D interconnected N- doped carbon network structure, featuring a carbon nitride backbone enclosed in graphitic carbon. The FeNi electrocatalyst (3DFeNiPDC) showed good bifunctional activity toward both ORR and OER in the basic medium with a low overpotential value of 30 mV for ORR and 6 mV for OER compared to its state-of-the-art counterparts Pt/C, and RuO2, respectively. Utilizing 3DFeNiPDC in a rechargeable Zn-air battery (RZAB) yields an open circuit voltage (OCV) of 1.35 V, a maximum power density of 232 mW cm-2, and an energy density of 707 W h kg-1. Additionally, a flexible RZAB employing 3DFeNiPDC demonstrates an OCV of 1.4 V with various bending angles. These finding suggest 3DFeNiPDC as a viable alternative to noble metal-based RZABs, offering superior bifunctional electrocatalytic activity and stability, particularly with its enhanced air-breathing properties facilitating improved operability under practical conditions. The bifunctional electrocatalytic activity of FeNi alloy nanoparticles embedded in a 3D- interconnected N-doped graphitic carbon (3DFeNiPDC) for both oxygen reduction and oxygen evolution is studied. The 3D architecture and core-shell characteristics of FeNi alloy nanoparticles provide better activity and stability for oxygen electrocatalysis. The electrocatalytic activity of 3DFeNiPDC has been exploited for liquid-state and solid-state flexible rechargeable zinc-air batteries. image
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

Aluminium, nitrogen-dual-doped reduced graphene oxide Co-existing with cobalt-encapsulated graphitic carbon nanotube as an activity modulated electrocatalyst for oxygen electrocatalyst for oxygen electrochemistry applications - Kharabe, Geeta Pandurang; Barik, Sidharth; Veeranmaril, Sudheesh Kumar; Nair, Aathira; Illathvalappil, Rajith; Yoyakki, Athira; Joshi, Kavita; Vinod, Chathakudath Prabhakaran; Kurungot, Sreekumar (Small, 2024)
There is a rising need to create high-performing, affordable electrocatalysts in the new field of oxygen electrochemistry. Here, a cost-effective, activity-modulated electrocatalyst with the capacity to trigger both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in an alkaline environment is presented. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with cobalt-encapsulated carbon nanotube units. Based on X-ray Absorption Spectroscopy (XAS) studies, it is established that the superior reaction kinetics in Al, Co/N-rGCNT over their bulk counterparts can be attributed to their electronic regulation. The Al, Co/N-rGCNT performs as a versatile bifunctional electrocatalyst for zinc-air battery (ZAB), delivering an open circuit potential approximate to 1.35 V and peak power density of 106.3 mW cm-2, which are comparable to the system based on Pt/C. The Al, Co/N-rGCNT-based system showed a specific capacity of 737 mAh gZn-1 compared to 696 mAh gZn-1 delivered by the system based on Pt/C. The DFT calculations indicate that the adsorption of Co in the presence of Al doping in NGr improves the electronic properties favoring ORR. Thus, the Al, Co/N-rGCNT-based rechargeable ZAB (RZAB) emerges as a highly viable and affordable option for the development of RZAB for practical applications. This manuscript reports the development of a new bifunctional catalyst that exhibits high activity and stability under practical operating conditions. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with the in situ formed cobalt-encapsulated CNT units is synthesized by a scalable pyrolysis method in an inert Ar atmosphere. The developed electrocatalyst achieved enhanced the oxygen reduction reaction (ORR) and the oxygen evolution reaction OER activity as a result of the favorable synergistic modulations and the system can serve as a process-friendly air-electrode for rechargeable zinc-air battery (RZAB). image
Keywords: Al; Bifunctional catalyst; DFT study; encapsulated structure; N-dual doping; Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable zinc-air battery; X-ray absorption spectroscopy

Advances in polymer electrolyte design strategies for highly efficient supercapacitors and Zn-based batteries - Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurian, Maria; Kurungot, Sreekumar (Chemical Communications, 2025)
Electrolytes play a crucial role in the performance of electrochemical energy storage systems, such as batteries and supercapacitors. Their main function is to act as a medium for ion transport between the electrodes, which is essential for the charge and discharge processes. Beyond this, the electrochemical performance of the device is strongly affected by the various properties of the electrolytes such as their ionic conductivity, chemical, thermal and electrochemical stability, chemical compatibility, etc. The intrinsic limitations of the aqueous electrolytes such as their decomposition during high voltage operations has led to the development of better electrolytes for batteries and supercapacitors. These included non-aqueous electrolytes, inorganic solid-state electrolytes, and gel polymer electrolytes. This feature article reviews the various approaches to designing a highly efficient polymer electrolyte for the targeted application along with the suitable device fabrication strategy adopted in the current literature to achieve a balanced electrochemical performance compared with a liquid electrolyte-based device.

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.